2019
DOI: 10.1097/aog.0000000000003610
|View full text |Cite
|
Sign up to set email alerts
|

Information Women Choose to Receive About Prenatal Chromosomal Microarray Analysis

Abstract: OBJECTIVE: To examine the choices of women with both high-risk and low-risk pregnancies who are undergoing prenatal chromosomal microarray analysis in a clinical setting regarding three challenging types of findings: variants of uncertain clinical significance, susceptibility loci for neurodevelopmental disorders, and copy number variants associated with risks for adult-onset conditions. We assessed whether women's choices were associated with indications for testing or with one-on-one pretest gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Regarding actionability, the same type of information was seen as worthwhile by those who chose to receive it, and superfluous by those who declined it. In a previous study, we showed that VUS were requested less often than SL and risks for adult‐onset conditions 3 . It has also been demonstrated that women are not likely to terminate pregnancy based on a VUS alone, that is, when ultrasound scans are normal 16 .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Regarding actionability, the same type of information was seen as worthwhile by those who chose to receive it, and superfluous by those who declined it. In a previous study, we showed that VUS were requested less often than SL and risks for adult‐onset conditions 3 . It has also been demonstrated that women are not likely to terminate pregnancy based on a VUS alone, that is, when ultrasound scans are normal 16 .…”
Section: Discussionmentioning
confidence: 92%
“…As previously detailed, about 60% of women undergoing amniocentesis in our center opt for testing because of advanced maternal age (AMA; with no abnormal findings in any of the biochemical screening tests and ultrasound scans) or personal wish, and the other 40% have a medical indication, such as abnormal ultrasound findings or a known monogenic disease. 3 All women undergoing amniocentesis are asked to indicate, as part of the consent process, which of the following findings they wish/do not wish to receive about their fetus: VUS, low-penetrant SL (10% and less), and CNVs associated with risk for adult-onset conditions. Prior to amniocentesis, women/couples met with a genetic counselor who provided an explanation about the various findings and answered questions.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations